Dampak Redenominasi terhadap Kinerja Perekonomian: Pendekatan Ekonomi Eksperimental - Annazah, Nur Siti; Juanda, Bambang; Mulatsih, Sri (UI Scholars Hub, 2018)
There is persistent debate between theoretical and empirical findings on the impact of redenomination on economic performance. Hence, this study aims to analyze the impacts of inflation, economic growth, reducing reducing digit (zero number), and stages of redenomination to changes in transaction prices and the number of the transactions using experimental methods. The result showed redenomination could decrease the transaction prices and transaction value. The best conditions to applied redenomination policy was directly in low inflation and high growth.